Benchmarking construction industry, company and project performance by participants' evaluation. Issue 7 (3rd October 2016) - Kärnä, Sami; Junnonen, Juha-Matti
Abstract : Purpose: The construction industry needs effective methods for gathering and utilizing performance information on industry, company and individual project levels. Such benchmarking (BM) information can be collected from project participants' bi-directional evaluations of each other's performance during construction projects. The purpose of this paper is to present the method and discuss the features of a multi-company project evaluation system as a BM tool. Also the accumulated results, based on the extensive BM database in the Finnish construction industry, are investigated. Design/methodology/approach: The web-based project evaluation tool was established in 2007 as a joint research project between the Helsinki University of Technology, construction organizations and main associations widely representing the construction industry in Finland. The evaluation method is based on soft, subjective measures, such as client satisfaction and project participants' satisfaction. The empirical observations of the study are based on over 5, 500 evaluations during which the BM system was used in the Finnish construction industry. Findings: The use of the evaluation is presented as a multi-level BM tool to evaluate the performance of different discipline groups on project, company and industry levels. The Finnish case shows an example of the industry-level performance BMs of project consultants, main contractors, sub-contractors and architects/designers. The BM categories include project management, staff, collaboration and project goal accomplishment. According to the results, the participants are satisfied with each other's performance. However, main development targets in the Finnish industry are related to risk management and managing design. Also, the development of sub-contractors' selection procedures will contribute to the performance of the industry. Research limitations/implications: The industry-level feedback is linked to the Finnish construction industry. Similar studies in other countries would enable international comparisons. Practical implications: Client satisfaction and project participants' satisfaction have been identified as one of the key factors affecting project success. With the help of mutual project evaluation, different BMs enable organizations to monitor their performance and to improve their operations in various areas. They also make it possible to position an organization's performance in comparison to the competitors and help to perceive black spots in the process on project level. As a common system for the parties in the industry, the project evaluation BM system promotes quality improvement, customer orientation and collaboration between participants. Social implications: Project evaluation between the project participants' enhance collaboration and mutual learning. Originality/value: Multi-company project evaluation is a new and promising topic in performance measurement which holds potential for performance improvement through the utilization of network information and team dynamics. The study presents its wider utility as the basis of national, company and project BM.